Comèl-Netherton syndrome – case report - Błażewicz, Izabela; Rustowska, Alicja; Wilkowska, Aleksandra; Nowicki, Roman (Dermatology Review/Przegląd Dermatologiczny, 2014)
Introduction. Comèl-Netherton syndrome is a rare autosomal recessive genodermatosis characterized by congenital ichthyosiform erythroderma, ichthyosis linearis circumflexa, trichorrhexis invaginata, and atopic diathesis. Comèl-Netherton syndrome is caused by mutations of the SPINK5 gene, which encodes the serine protease inhibitor LEKTI. Objective. We present diagnostic and therapeutic difficulties in a patient with Comèl-Netherton syndrome. Case report. We present the case of a 3-year-old boy, in whom from the first day of life generalized ichthyosiform erythroderma and diffuse exfoliation of the skin were observed. The differential diagnosis included Omenn syndrome, and atopic and seborrheic dermatitis. Finally, based on the overall clinical picture and microscopic examination of the hair, which showed the presence of bamboo hair, Comèl-Netherton syndrome was diagnosed. Conclusions . Because of similarity to other erythroderma, diagnosis of Comèl-Netherton syndrome in the first months of life creates diagnostic problems. In older children, recurrent skin infections and atopic diathesis can cause therapeutic difficulties and require the cooperation of many specialists.